Zoning In on Transit-Oriented Development: Understanding Bylaw Reform as Critical Policy Groundwork - Soliz, Aryana; Rodrigue, Lancelot; Peaker, Christian; Bernard, Isabelle; El-Geneidy, Ahmed (Journal of the American Planning Association, 2024)
Transit-oriented development (TOD) has been widely encouraged as a strategy to limit urban sprawl, increase urban density, and enhance neighborhood diversity. Federal and regional governments have been increasingly promoting such TOD in parallel with light rail transit (LRT) projects to foster sustainable transitions. Little is known, however, about the processes through which municipalities have made changes to existing land use regulations to achieve TOD goals. In this article we trace changes in municipal plans and bylaws surrounding a CA$7 billion LRT in Montréal (Canada) that opened in summer 2023, 7 years after its announcement. Specifically, we analyzed whether changes in municipal bylaws conformed to TOD plans recommended by the metropolitan government while exploring local barriers to zoning reform. Through policy and spatial analysis, we found that only a limited number of municipalities made sufficient bylaw changes between 2016 and 2022 to support TOD plans aimed at implementing mixed-use zoning, increasing urban density, and reducing parking ratios. Through an analysis of rezoning processes, we see an opportunity for improved multilevel cooperation, public engagement activities, and positive communication strategies in the process of building integrated transport and land use systems. These findings can aid planners and policymakers in understanding the importance of reforming municipal zoning bylaws and regional approaches to TOD, strengthening collaboration between different levels of government, and engaging in meaningful public consultation practices to foster an integrated transport and land use approach. If LRT projects are to be successful in meeting sustainability goals, greater engagement with land use regulations across multiple scales is needed to facilitate TOD.